In Situ Growth of Crystalline and Polymer‐Incorporated Amorphous ZIFs in Polybenzimidazole Achieving Hierarchical Nanostructures for Carbon Capture. Issue 23 (12th May 2022) - Hu, Leiqing; Bui, Vinh T.; Pal, Sankhajit; Guo, Wenji; Subramanian, Ashwanth; Kisslinger, Kim; Fan, Shouhong; Nam, Chang‐Yong; Ding, Yifu; Lin, Haiqing
Abstract: Mixed matrix materials (MMMs) hold great potential for membrane gas separations by merging nanofillers with unique nanostructures and polymers with excellent processability. In situ growth of the nanofillers is adapted to mitigate interfacial incompatibility to avoid the selectivity loss. Surprisingly, functional polymers have not been exploited to co‐grow the nanofillers for membrane applications. Herein, in situ synergistic growth of crystalline zeolite imidazole framework‐8 (ZIF‐8) in polybenzimidazole (PBI), creating highly porous structures with high gas permeability, is demonstrated. More importantly, PBI contains benzimidazole groups (similar to the precursor for ZIF‐8, i.e., 2‐methylimidazole) and induces the formation of amorphous ZIFs, enhancing interfacial compatibility and creating highly size‐discriminating bottlenecks. For instance, the formation of 15 mass% ZIF‐8 in PBI improves H2 permeability and H2 /CO2 selectivity by ≈100% at 35 °C, breaking the permeability/selectivity tradeoff. This work unveils a new platform of MMMs comprising functional polymer‐incorporated amorphous ZIFs with hierarchical nanostructures for various applications. Abstract : In situ growth of ZIFs in polybenzimidazole (PBI) generates bimodal free volumes from tightly packed amorphous ZIF‐8 (induced by PBI) and highly porous crystalline ZIF‐8. Such hierarchical nanostructures improve H2 permeability and H2 /CO2 selectivity simultaneously, overcoming the permeability/selectivity tradeoff. The study unveils an important yet often neglected role of functional polymers in designing mixed matrix materials for various applications.